PENGARUH LAYANAN PELENGKAP TERHADAP KEPUASAN PELANGGAN PADA TOKO MEUBEL SYAKIRA DI TENGGARONG - Bahaa’uddin, Elfreda Aplonia Lau, Umi Kulsum (RJABM (Research Journal of Accounting and Business Management), 2018)
This study aims to analyze the influence of complementary services from the dimensions of information, consultation, order taking, hospitality, care taking, exceptions, billing and payment for customer satisfaction at the Syakira Furniture Store. . Respondents used in this study were 97 customers. The results showed that partially, the information, hospitality, exceptions (exceptions) variables had a significant effect on customer satisfaction at the Syakira Furniture Shop. While consulting variables, order taking variables, care taking variables, billing variables have no significant effect on customer satisfaction. Simultaneously, information variables, consultation, order taking, hospitality, care taking, exceptions, billing and payments have a significant effect on customer satisfaction.